(untitled) (Marketing Journal, 2025)
This study analyzes the effectiveness of digital marketing tools in the context of modern tourism. User behavior is examined through the lens of the Push –Pull– Resistance model. A comparative evaluation of Social Media, Email marketing, and SEO strategies i s conducted to assess their impact on conversion, trust -building, and technical efficiency. In addition, a SWOT analysis reveals the strengths and 576 weaknesses of social media marketing, while the integration of technologies such as AI, VR, and chatbots is explored as a means to enhance user experience. The findings underscore the strategic role of digital marketing in influencing tourist decision -maki ng and provide practical recommendations for tourism professionals.